CHANGESINTHEEXPRESSIONOFADIPONECTINANDITSRECEPTORS(A DIPOR1 ANDADIPOR2)INSEXUALLYIMMATUREANDSEXUALLYMATURESHEEPTESTES - ManBai; LiminSun; JiaZhao; GuishanZhang; WeiMa; LujieXiang; JiarongLi; ChaoJia; andHuaizhiJiang. (Journal of Animal and Plant Sciences, 2018)
Recentevidenceshaveindicatedthatadiponectinanditsreceptorshaveaneffectonmalereproduction.Theobjectiveof thisstudywastodetecttheexpressionofadiponectin,AdipoR1andAdipoR2insexuallyimmatureandsexuallymature sheeptestesusingqRT-PCRandWesternblot.Theresultsshowedthatadiponectin,AdipoR1andAdipoR2wereall expressed insheep testes. The expressionof AdipoR1 and AdipoR2 mRNAs(p<0.05 and p<0.01) as wellas the expressionofAdipoR1andAdipoR2proteins(p<0.01andp<0.05)insexuallymaturetestesweresignificantlyhigher thanthatinsexuallyimmaturetestes.However,therewasnosignificantdifferenceintheexpressionof adiponectin mRNA(p>0.05)insexuallyimmatureandsexuallymaturetestes,theexpressionofadiponectinproteininsexually maturetesteswassignificantlyhigherthanthatinsexuallyimmaturetestes(p<0.01).Itisthefirsttimetocomparethe mRNAandproteinexpressionofadiponectinanditsreceptorsinsexuallyimmatureandsexuallymaturesheeptestes. and AdipoR2wereexpressedinhumanandratpituitary
Keywords: adiponectin; AdipoR1; AdipoR2; sheep; testes; qRT-PCR; Western-blot